2014
DOI: 10.1016/j.surg.2014.08.061
|View full text |Cite
|
Sign up to set email alerts
|

The importance of sonographic landmarks by transcutaneous laryngeal ultrasonography in post-thyroidectomy vocal cord assessment

Abstract: Each sonographic landmark had similar reliability and diagnostic accuracy. Identifying all 3 sonographic landmarks was not mandatory and visualizing normal movement in one of the sonographic landmarks would be sufficient to exclude VCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 16 publications
3
56
0
Order By: Relevance
“…8,10 In this regard, TLUSG has become an alternative to investigate laryngeal sequelae in surgical cases involving the anterior cervical region, such as a thyroidectomy. 3,4,7 Thyroidectomy is the preferred surgery for the treatment of certain thyroid diseases 11 and is one of the most frequently performed procedures in the world. Although it is considered a safe procedure, with low morbidity and mortality close to 0%, 12 it can cause laryngeal immobility or vocal fold immobility as iatrogenic factors, which compromise the vocal pattern, impair swallowing, and lead to significant complications in the patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,10 In this regard, TLUSG has become an alternative to investigate laryngeal sequelae in surgical cases involving the anterior cervical region, such as a thyroidectomy. 3,4,7 Thyroidectomy is the preferred surgery for the treatment of certain thyroid diseases 11 and is one of the most frequently performed procedures in the world. Although it is considered a safe procedure, with low morbidity and mortality close to 0%, 12 it can cause laryngeal immobility or vocal fold immobility as iatrogenic factors, which compromise the vocal pattern, impair swallowing, and lead to significant complications in the patient's quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 By contrast, TLUSG is not invasive, uncomfortable, or painful and has been described by some studies as a viable and reliable examination to assess laryngeal function. 4,17,18 Since the test may be performed in real-eating situations and even at the bedside, TLUSG has also been used for the assessment of some biomechanical swallowing parameters to complement the functional assessment of patients with oropharyngeal dysphagia. 19,20 Although the literature describes TLUSG as an alternative to assess the functional integrity of the larynx, it is still necessary to better understand the situations in which this examination can be effectively included in thyroidectomy clinical routine.…”
Section: Introductionmentioning
confidence: 99%
“…In a larger cohort, Wang et al reported that vocal fold motion using US could be assessed in 87% of patients, and that it was less observable in male subjects and in older patients . Recently, US has been proposed in surgery research to assess vocal fold motion during breathing at rest and detect recurrent nerve paralysis after thyroid surgery . It was proposed to estimate the symmetry of the laryngeal tract in abduction and adduction, and diagnosis of recurrent nerve paralysis was based on the visual impression of vocal fold immobility.…”
mentioning
confidence: 99%
“…Most of these studies reported visual criteria to assess the vocal fold motion. Current debates deal with the choice of appropriate landmarks (true vocal folds, false vocal folds, or arytenoids); the choice of the acquisition plane (axial or lateral view); the choice of observation condition (free breathing, phonation, or Valsalva maneuver); and the development of the method in multiple institutions using various US scanners …”
mentioning
confidence: 99%
See 1 more Smart Citation